Fluctuations of viti- and oleiculture traditions in the Bronze and Iron Age Levant - Simone Riehl; Katleen Deckers; Israel Hinojosa-Baliño; Darren R. Gröcke; Dan Lawrence (PLoS ONE, 2025)
Various researchers have demonstrated periods of instability in the cultivation of olives and grapes in the eastern Mediterranean, dating back at least to the Early Bronze Age. So far, pollen-based studies have focused primarily on olive cultivation in the southern Levant. Our research extends these studies to include both cash crops throughout the Levant and northern Mesopotamia, including several different climatic zones, to better understand the diversity of human strategies for maintaining agricultural stability. We analysed 1,514 charred olive (Olea europaea) and grape (Vitis vinfera) seed and wood samples from archaeological sites for their stable carbon isotope ratios to reconstruct Bronze and Iron Age growing conditions. The results, with generally 3.7‰ higher Δ13C values in grapevine than in olive, are consistent with the physiological characteristics of the two species, i.e., their water use efficiency, and with their different agronomic needs. Furthermore, higher values in charcoals than in fruits indicate the natural differences in the budgets of water availability associated with the period of formation of the measured plant tissue. Canonical correspondence analysis (CCA) of the complete data set shows clear correlation of the mean Δ13C values with reconstructed average precipitation (RAP) and the general north-south and west-east decline in precipitation of the region, as well as with chronology, including a gradual drying trend through time. Principal component analysis (PCA) based on these variables shows a highly diversified relationship between mean and maximum stress levels and RAP at different sites over time. An important trend is the significant accumulation of Iron Age sites in olive-growing and wine-producing regions above 500 mm RAP. However, there are considerable diachronic differences in the stress signals for the two tree crops. Interpolations of the mean Δ13C values of the crop species are in good agreement with the layout of the isohyets and visualize the PCA patterns of stable carbon isotope and precipitation relationships thereby confirming the major trends such as a better water availability in the Iron Age. The well-known major climatic fluctuations at 4.2 and 3.2 kyr BP correlate with likely irrigation of olive trees, while there are also drought patterns indicated in the Δ13C values at the end of the Middle Bronze Age. In general, the greater commitment to the establishment of agricultural niches and successful production for viticulture compared to oleiculture, which has already been observed in historical times, is confirmed, at least since the Middle Bronze Age and especially in the Iron Age.